Effects of lactic acid bacteria inoculants on fermentation characteristics and microbial community profiles of napier grass (Pennisetum purpureum) silage - ROHMATUSSOLIHAT ROHMATUSSOLIHAT; RONI RIDWAN; AINISSYA FITRI; KI AGENG SARWONO; WULANSIH DWI ASTUTI; DUDI FIRMANSYAH; YANTYATI WIDYASTUTI; ARIO BETHA JUANSSILFERO; RUSLI FIDRIYANTO; MUHAMMAD RIDLA; NISA RACHMANIA MUBARIK; ANURAGA JAYANEGARA (Society for Indonesian Biodiversity, 2026)
Abstract. Rohmatussolihat, Ridwan R, Fitri A, Sarwono KA, Astuti WD, Firmansyah D, Juanssilfero AB, Fidriyanto R, Ridla M, Mubarik NR, Jayanegara A. 2026. Effects of lactic acid bacteria inoculants on fermentation characteristics and microbial community profiles of napier grass (Pennisetum purpureum) silage. Biodiversitas 27 (4): d270438. https://doi.org/10.13057/biodiv/d270438. Napier grass (Pennisetum purpureum) is an important tropical forage; however, its high moisture content and low water-soluble carbohydrates (WSC) often impair silage fermentation. This study evaluated the effects of different lactic acid bacteria (LAB) inoculants on fermentation characteristics, nutrient preservation, and microbial community dynamics of napier grass silage. Four indigenous LAB strains, Companilactobacillus kimchii InaCC-B982, Lactiplantibacillus plantarum InaCC-B1028, Limosilactobacillus fermentum InaCC-B1024, and Levilactobacillus brevis InaCC-B1052, were applied individually and as a mixed inoculum and compared with an uninoculated control. Silage was sampled after 7, 14, and 28 days. LAB inoculation significantly improved fermentation quality compared with the control by accelerating acidification, lowering pH (3.69-3.86), increasing lactic acid concentration (2.38-4.90% DM), and suppressing yeasts and coliform bacteria. Among the inoculants, L. plantarum InaCC-B1028 showed the most consistent and superior performance, characterized by rapid and stable pH reduction (3.73-3.78), higher lactic acid production, minimal ammonia-N accumulation (≤0.08% DM), and improved crude protein retention (8.7-9.2% DM). In contrast, L. brevis and the mixed LAB treatment resulted in higher acetic acid concentrations, suggesting enhanced aerobic stability but less consistent nutrient preservation, whereas L. fermentum exhibited intermediate effects. Metagenomic analysis revealed that the bacterial community was dominated by Lactiplantibacillus and Companilactobacillus, with species such as L. plantarum, L. pentosus, L. paraplantarum, and C. kimchii contributing to fermentation dynamics. Genus-level dominance was consistent with species-level composition, indicating robust taxonomic structure across hierarchical levels. Overall, L. plantarum InaCC-B1028 is the most effective inoculant for improving fermentation efficiency, nutrient preservation, and microbial stability, highlighting its potential for enhancing silage quality in tropical forage systems.